A Common Fixed Point Theorem for Two Compatible Self-maps of a \(S\)-Metric Space - Kiran, V.; Goud, J. Niranjan (Communications in Mathematics and Applications, 2022)
In this paper, we prove a common fixed point theorem for two compatible self-maps of a \(S\)-metric space.
Keywords: S-metric space; Fixed point; Contractive modulus; Associated sequence of a point relative to two self maps